2014
DOI: 10.1002/ange.201408205
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Synthesis of Atropisomeric Biaryls: A Cation‐Directed Nucleophilic Aromatic Substitution Reaction

Abstract: A catalytic enantioselective nucleophilic aromatic substitution reaction which yields axially chiral biaryl derivatives in excellent yields with e.r. values of up to 97:3 has been developed. This process uses a chiral counterion to direct the addition of thiophenolate to a prochiral dichloropyrimidine by a tandem desymmetrization/kinetic resolution mechanism. The products can be derivatized to a range of atropisomeric structures without any reduction in enantioenrichment, thus offering access to unexplored chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…27,28 In support of the feasibility of an atroposelective addition, the nucleophilic addition of thiophenols is a well-studied topic in enantioselective catalysis, 29 exemplified by work by Wynberg. 30,31 Furthermore, work from Smith 32 and a recent kinetic resolution from our group 33 have shown that chiral quaternary ammonium salts can effect atroposelective thiophenol addition via S N Ar.…”
mentioning
confidence: 99%
“…27,28 In support of the feasibility of an atroposelective addition, the nucleophilic addition of thiophenols is a well-studied topic in enantioselective catalysis, 29 exemplified by work by Wynberg. 30,31 Furthermore, work from Smith 32 and a recent kinetic resolution from our group 33 have shown that chiral quaternary ammonium salts can effect atroposelective thiophenol addition via S N Ar.…”
mentioning
confidence: 99%
“…Owing to the importance of this structural motif, the catalytic atroposelective construction of axially chiral biaryls has been intensively investigated 1 2 3 4 5 6 and could be accessed by enantioselective oxidative/cross coupling of two aryl counterparts, 7 8 9 10 11 12 13 asymmetric construction of an aromatic ring 14 15 16 17 18 19 20 and kinetic resolution/desymmetrization of biaryl compounds ( Fig. 1a , left) 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 . However, in sharp contrast, the axially chiral styrenes bearing a chiral axis between a simple alkene and an aromatic ring have been rarely studied with respect to asymmetric synthesis and applications 37 38 .…”
mentioning
confidence: 99%
“…While advances in large-scale analytical separations and resolutions would certainly improve this situation, the ultimate solution will likely also need to include the development of new atroposelective methodologies (both catalytic and auxiliary based) that can be employed on many of the common atropisomeric scaffolds in drug discovery including heterobiaryls, diaryl ethers and diaryl amines. While there has been seminal examples in the literature over the past decade, the field of atroposelective synthesis is much less studied than that of point chirality, with the majority of atroposelective examples being studied on biaryls [11,[70][71][72][73][74][75][76][77][78][79]. As controlling atropisomer conformation becomes a more prevalent strategy in drug discovery we expect there to be increasing need and opportunities for the development of innovative new atroposelective methodologies and expect that the field will be up for the challenge.…”
Section: Future Perspectivementioning
confidence: 99%